Revolution I love you : 1968 in art, philosophy - Fowkes, Maja; Fowkes, Reuben; International Project Space, Birmingham (Birmingham : International Project Space Birmingham, 2008)
Bunting, Heath ; Davenport, Nancy ; Erhardt, Miklos ; Ganne, Jean-Baptiste ; Kwiekulik ; Lulic, Marko ; Nemes, Csaba ; Ressler, Oliver ; Begg, Zanny ; RugaNegra ; St. Auby, Tamas ; Sandlund, Fia-Stina ; Stilinovic, Mladen ; Tsivopoulos, Stefanos
Published on the occasion of the exhibition "Revolution, I love you" at the International Project Space in Birmingham, 13.11.2008 - 19.12.2008
boek